A comparison of box-to-box and positional possession styles: selecting an appropriate game format for U13 footballers (a pilot study) - Bleidelis, Imants; Luika, Signe; Kolesovs, Aleksandrs; Boobani, Behnam (Frontiers in Sports and Active Living, 2025)
IntroductionThis pilot study aimed to examine trends in the use of game zones, group interactions of players participating in a game episode, and the effectiveness of their actions in the completion zone for the age group U13, between the game formats 9 vs. 9 and 11 vs. 11.MethodsLatvian Football Players (n = 45), six goalkeepers and 39 field players, 12.6 ± 0.7 years of age; height: 1.65 ± 0.18 m; weight: 54.3 ± 10.2 kg; BMI: 26.7 ± 3, in three teams (from Riga), played two one-day tournaments (game order: C-B, C-A, and B-A) using two competition formats. A quasi-experimental design was used to assess the tendencies of changes in game format. Observational methodologies were used to analyze the six match recordings by the Lince 2.1 computer program, recorded with two VEO Gen.2 cameras, to evaluate the start and end zones of game episodes, including shots at the opponent's goal.ResultsIt was found that when choosing between the formats 9 vs. 9 and 11 vs. 11 in the U13 age group, it is possible to expect visible change (based on a medium effect size) in distribution of start and end of game episodes with more often reaching the completion zone, (the 1/3 area of the field where the opponent's goal was located), increasing number of players involved in the game episode, and the increasing number of cases of changing the direction of the attack under 9 vs. 9 format.ConclusionThe results showed that when choosing the format of youth championships, coaches and stakeholders should consider its impact on the formation of game patterns in players.